A carboxy-terminal trimerization domain stabilizes conformational epitopes on the stalk domain of soluble recombinant hemagglutinin substrates. - Florian Krammer; Irina Margine; Gene S Tan; Natalie Pica; Jens C Krause; Peter Palese (PLoS ONE)
Recently, a new class of broadly neutralizing anti-influenza virus antibodies that target the stalk domain of the viral hemagglutinin was discovered. As such, induction, isolation, characterization, and quantification of these novel antibodies has become an area of intense research and great interest. Since most of these antibodies bind to conformational epitopes, the structural integrity of hemagglutinin substrates for the detection and quantification of these antibodies is of high importance. Here we evaluate the binding of these antibodies to soluble, secreted hemagglutinins with or without a carboxy-terminal trimerization domain based on the natural trimerization domain of T4 phage fibritin. The lack of such a domain completely abolishes binding to group 1 hemagglutinins and also affects binding to group 2 hemagglutinins. Additionally, the presence of a trimerization domain positively influences soluble hemagglutinin stability during expression and purification. Our findings suggest that a carboxy-terminal trimerization domain is a necessary requirement for the structural integrity of stalk epitopes on recombinant soluble influenza virus hemagglutinin.